2017
DOI: 10.1111/njb.01255
|View full text |Cite
|
Sign up to set email alerts
|

Psydrax multiflora sp. nov. (Rubiaceae) from Palawan, Philippines

Abstract: Psydrax multiflora, a new species of Vanguerieae collected in the Palawan, Luzon Island, Philippines is herein described and illustrated. Morphological observation showed that P. multilfora approaches three Malesian Psydrax species, namely P. amplifolia, P. nitida and P. puberula. However, P. multiflora can be delineated from these three by its caudate leaf apex, 20–30‐flowered umbellate inflorescences and broadly triangular corolla lobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…(the remaining part of Canthium after the reinstatement of Psydrax and Keetia ) and Psydrax can be distinguished distinctively by the anatomical features of their leaves and young stems (Tilney et al 1990 , 1988 ), while Keetia can be distinguished morphologically from Psydrax by its pyrene, anther and carlyx-limb (Bridson 1986 ; Lantz et al 2002 ). Psydrax species go with varying synonyms which are adopted by different authors, and their number keeps increasing as new species, which are yet to be included in The Plant List database, are being discovered (Arriola and Alejandro 2013 ; Arriola et al 2017 ; Mahyuni et al 2019 ). In 2020, a new species, P. gialaiensis , was discovered in Gia Lai Province, Southern Vietnam (Quang et al 2020 ) and has been uploaded on the website of the World Checklist of Selected Plant Families(WCSP) alongside another new species, Psydrax lanceolatus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(the remaining part of Canthium after the reinstatement of Psydrax and Keetia ) and Psydrax can be distinguished distinctively by the anatomical features of their leaves and young stems (Tilney et al 1990 , 1988 ), while Keetia can be distinguished morphologically from Psydrax by its pyrene, anther and carlyx-limb (Bridson 1986 ; Lantz et al 2002 ). Psydrax species go with varying synonyms which are adopted by different authors, and their number keeps increasing as new species, which are yet to be included in The Plant List database, are being discovered (Arriola and Alejandro 2013 ; Arriola et al 2017 ; Mahyuni et al 2019 ). In 2020, a new species, P. gialaiensis , was discovered in Gia Lai Province, Southern Vietnam (Quang et al 2020 ) and has been uploaded on the website of the World Checklist of Selected Plant Families(WCSP) alongside another new species, Psydrax lanceolatus.…”
Section: Introductionmentioning
confidence: 99%
“…Bridson and other group of researchers (Bridson 1985 ; Lantz et al 2002 ) reported that more than thirty species of the genus are native to Africa, and these are not far from the WCSP’s list of continental distribution of 54 species of the genus in different countries in Africa. Though, Psydrax is the largest genus in its tribe, some of its species are rare and at the verge of extinction (Cheek and Sonké 2004 ; Subashree et al 2021 ), and their decreasing population may be ascribed to their traditional uses (Arriola et al 2017 ; Tabuti et al 2009 , 2011 ).…”
Section: Introductionmentioning
confidence: 99%